2019
DOI: 10.1183/13993003.00194-2019
|View full text |Cite
|
Sign up to set email alerts
|

Population-based prevalence of bronchiectasis and associated comorbidities in South Korea

Abstract: Bronchiectasis is a chronic respiratory disease characterised by abnormal dilatation of bronchi, which presents clinically with cough, sputum production and recurrent infection [1]. Although bronchiectasis had been regarded as an "orphan" disease [2], recent studies have shown that the prevalence of bronchiectasis is increasing and this disease causes a significant burden on public health, including increased healthcare costs, hospital admission and mortality [3][4][5].Data on the prevalence of bronchiectasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
98
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(110 citation statements)
references
References 14 publications
3
98
4
Order By: Relevance
“… 8 , 22 , 23 Bronchiectasis was defined using the ICD-10 diagnosis code J47 (bronchiectasis). 24 Subjects with cystic fibrosis (ICD-10 diagnosis code E84) were excluded.…”
Section: Methodsmentioning
confidence: 99%
“… 8 , 22 , 23 Bronchiectasis was defined using the ICD-10 diagnosis code J47 (bronchiectasis). 24 Subjects with cystic fibrosis (ICD-10 diagnosis code E84) were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Because the KMBARC registry is based on the framework of the EMBARC protocol, collaborative studies involving the two may help unravel racial differences in the aetiologies and phenotypes of bronchiectasis as well as bronchiectasis comorbidities 4. There is reason to suspect racial and ethnic differences in many aspects of bronchiectasis since we have demonstrated lower prevalence of COPD and cardiovascular diseases in the Korean population than in the Western population 6 38. However, the reasons for these ethnic differences remain unclear due to insufficient information contained in the national health insurance database.…”
Section: Discussionmentioning
confidence: 95%
“…Despite the lack of epidemiological data in Korea, epidemiological studies have demonstrated that bronchiectasis poses a significant burden on public health, including increased healthcare costs, hospital admission and mortality 20–22. Therefore, we conducted a nationwide database study on the prevalence of bronchiectasis in Korea 6. Our study demonstrated that the prevalence of non-cystic fibrosis bronchiectasis was 464 cases per 100 000 population, which was strikingly higher than that reported in Germany (67 cases per 100 000 population) and the USA (138 cases per 100 000 population) 23 24.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bronchiectasis is increasing in prevalence and escalates the public health burden, resulting in increased health care costs, hospitalization rates, and mortality 2,3 . A recent study in Korea using a government health insurance database showed that the prevalence of bronchiectasis in Korea was higher than that in other Western countries, and the healthcare cost was high 4 . In addition to the high prevalence and economic burden, assessment of health-related quality of life (HRQOL) is important in chronic diseases such as bronchiectasis, as it can evaluate the overall impact on health from the patient' s point of view.…”
Section: Introductionmentioning
confidence: 99%